Perencanaan Pengembangan Aset Fasilitas Taman Rekreasi Geopark Batu Mahpar Kabupaten Tasikmalaya Berdasarkan Konsep Geowisata - Dwiyanto, Lutfi; Purwihartuti, Koernia (Jurnal Pariwisata Terapan, 2023)
The asset quality issues of the Batu Mahpar facility consist of: 1) There are no interpretation panels and miniature geological features, planting fields, foot-cleaning basins, life guard chairs, camp area dividers, five types of dining places, fire extinguishers, lighting, shopping facilities, car parking lots, bridges, information centers, and 2) The condition of facility assets includes physical outbound rides that are not suitable for operation, ten damaged photo spots, unclear designation of animal cages, trash bins are not differentiated by type, toilets in the waterfall area are dirty and not functioning, and the location of the activation counter is not strategic. The research objective was to plan the development of Batu Mahpar facility assets based on the geotourism concept. The research method is descriptive with qualitative and quantitative approaches. Data collection techniques include observation, interviews, documentation. The results are development plan for 15 indicators of Batu Mahpar facility assets as follows: 1) Physical includes the construction of miniature Batu Mahpar, outbound rides, planting land, rental counters, foot-cleaning basins, and animal cages, procurement of interpretation panels, plant vegetation, life guard chairs, giant sliders, photo spots; 2) Accommodation includes the construction of halls, warehouses, and culinary kiosks, procurement of camp area dividers, food corner booths, supporting equipment; 3) Support facilities include the construction of viewing towers, visitor needs kiosks, souvenir kiosks, toilets, parking lots, and bridges, procurement of fire extinguishers, trash cans, supporting equipment; 4) Tourism support facilities include the construction of information centers and activation counters and procurement of equipment and furniture.